2014
DOI: 10.1007/s11606-014-3056-x
|View full text |Cite
|
Sign up to set email alerts
|

A Failure to Communicate: A Qualitative Exploration of Care Coordination Between Hospitalists and Primary Care Providers Around Patient Hospitalizations

Abstract: Hospitalists and PCPs encounter similar challenges in care coordination, yet have important experiential differences related to sending and receiving roles for hospital discharges. Efforts to improve coordination of care between hospitalists and PCPs should aim to understand perspectives of clinicians in each setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
146
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(153 citation statements)
references
References 10 publications
5
146
0
2
Order By: Relevance
“…26,27 Breakdowns in communication are common when patients are discharged from one setting to another, such as from the hospital to home. 28 Because family members and friends often bridge settings alongside patients, 26,29 timely access to accurate information about the patient's health and discharge plan could improve transitional care 30 and help avert risky or redundant diagnostic procedures when a patient is incapacitated and unable to communicate.…”
Section: Capturing and Executing Patient Preferences For Familymentioning
confidence: 99%
“…26,27 Breakdowns in communication are common when patients are discharged from one setting to another, such as from the hospital to home. 28 Because family members and friends often bridge settings alongside patients, 26,29 timely access to accurate information about the patient's health and discharge plan could improve transitional care 30 and help avert risky or redundant diagnostic procedures when a patient is incapacitated and unable to communicate.…”
Section: Capturing and Executing Patient Preferences For Familymentioning
confidence: 99%
“…1,2 Despite financial incentives and growing attention from the medical community, significant inter-provider variability exists with regard to perceived responsibility in the post-discharge period. 3,4 A recent study of practicing hospitalists found that 29 % believed their responsibility for patients ended at the time of discharge, while 26 % believed their responsibility extended beyond 2 weeks. 5 Primary care providers express similar variability regarding the timing and content of their responsibility for patients after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…5 Primary care providers express similar variability regarding the timing and content of their responsibility for patients after discharge. 4,6 As a result, a responsibility gap often exists for recently discharged patients in which the delineation between inpatient and outpatient provider responsibilities is undefined.…”
Section: Introductionmentioning
confidence: 99%
“…5 Their portrait of a care period characterized by unclear provider accountability and inadequate knowledge on the part of both providers and patients is painfully familiar to those who treat patients across the post-hospital care transition. 6 Their findings are disquieting but not altogether surprising: an implicit lack of investment in the transitional care of the discharged patient that providers attribute to inadequate time, failures of communication attributed to poor technological resources in systems that continue to depend largely on one-way pager and fax technology, and persistent clinical loose ends despite proliferation of health information technology.…”
mentioning
confidence: 99%